2009
DOI: 10.1111/j.1567-1364.2009.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans iron acquisition within the host

Abstract: As a commensal and opportunistic pathogen, Candida albicans possesses a range of determinants that contribute to survival, persistence and virulence. Among this repertoire of fitness and virulence attributes are iron acquisition factors and pathways, which allow fungal cells to gain this essential mineral in the iron-poor environment of the host. The aim of this review is to present the strategies used by C. albicans to exploit host iron reservoirs and their impact on C. albicans pathogenicity. Because iron in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 118 publications
(232 reference statements)
2
183
0
Order By: Relevance
“…Despite reports of the inhibitory effects of lactoferrin and transferrin on pathogenic fungi (Almeida et al, 2009;Caza & Kronstad, 2013), Candida albicans and Aspergillus fumigatus can both utilize transferrin bound iron for growth using different mechanisms (Ramanan & Wang, 2000;Hissen et al, 2004). Siderophores are not involved in iron acquisition by Candida albicans; rather direct contact of Candida albicans with transferrin is required.…”
Section: Iron Acquisition From Host Iron-binding Proteinsmentioning
confidence: 99%
“…Despite reports of the inhibitory effects of lactoferrin and transferrin on pathogenic fungi (Almeida et al, 2009;Caza & Kronstad, 2013), Candida albicans and Aspergillus fumigatus can both utilize transferrin bound iron for growth using different mechanisms (Ramanan & Wang, 2000;Hissen et al, 2004). Siderophores are not involved in iron acquisition by Candida albicans; rather direct contact of Candida albicans with transferrin is required.…”
Section: Iron Acquisition From Host Iron-binding Proteinsmentioning
confidence: 99%
“…Thus, the ability of C. albicans to acquire iron becomes critical for its survival as well as for pathogenesis (31). As in S. cerevisiae, there are multiple pathways for iron uptake in C. albicans as well, including high-affinity uptake, siderophore uptake, and heme uptake (32)(33)(34)(35). Previous reports showed that FTR1 is required for C. albicans pathogenesis (33).…”
Section: From the School Of Life Sciences Jawaharlal Nehru Universitmentioning
confidence: 99%
“…The C. albicans genome contains genes encoding siderophore transporter, four iron permeases, five multicopper oxidases, a family of 17 putative ferric reductases, as well as heme uptake components indicating the multiplicity of iron acquisition pathways (28,32). C. albicans can also acquire iron from ferritin in a manner dependent on the Als3 protein (36), but, iron acquisition through Als3/ferritin does not exist in S. cerevisiae.…”
Section: From the School Of Life Sciences Jawaharlal Nehru Universitmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ferritin is extremely resistant to microbial exploitation, C. albicans is able to use it as an iron source through the glycosylphosphatidylinositol (GPI)-anchored cell wall protein Als3, which not only functions as an adhesin and invasin but also serves as the receptor for ferritin (Almeida et al, 2008). To release and use iron from transferrin and ferritin or to exploit free environmental iron, C. albicans employs the reductive pathway, as reviewed by Almeida et al (2009). First, plasma membrane-located ferric reductases, like Fre10 and Cfl1, reduce ferric iron (Fe 3+ ) to the more soluble ferrous form (Fe 2+ ) (Knight et al, 2005;Yamada-Okabe et al, 1996).…”
Section: Introductionmentioning
confidence: 99%